2016
DOI: 10.1002/humu.23054
|View full text |Cite
|
Sign up to set email alerts
|

TMEM231Gene Conversion Associated with Joubert and Meckel-Gruber Syndromes in the Same Family

Abstract: Joubert and Meckel-Gruber syndromes (JS and MGS) are ciliopathies with overlapping features. JS patients manifest the "molar tooth sign" on brain imaging and variable eye, kidney, and liver disease. MGS presents with polycystic kidneys, occipital encephalocele, and polydactyly; it is typically perinatally fatal. Both syndromes are genetically heterogeneous; some genes cause either syndrome. Here, we report two brothers married to unrelated women. The first brother had three daughters with JS and a son with pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 19 publications
3
18
0
Order By: Relevance
“…The expected exon 4 deletion could not be validated by this analysis, but we instead observed four clustered substitution variants (c.742‐1G>A, c.742A>G, c.747C>T, and c.752T>C) that were present in the long‐read, but not the short‐read, datasets (Figure ). The same clustered variants have previously been observed and attributed to a gene conversion event occurring between TMEM231 and a pseudogene located approximately 40 kb downstream (centromeric) from the functional gene (Maglic et al, ). It, therefore, appeared that during alignment, reassignment of short reads containing pseudogene‐derived variants, from TMEM231 to the more closely‐matching pseudogene locus, was the explanation for the apparent loss of read‐depth at exon 4.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…The expected exon 4 deletion could not be validated by this analysis, but we instead observed four clustered substitution variants (c.742‐1G>A, c.742A>G, c.747C>T, and c.752T>C) that were present in the long‐read, but not the short‐read, datasets (Figure ). The same clustered variants have previously been observed and attributed to a gene conversion event occurring between TMEM231 and a pseudogene located approximately 40 kb downstream (centromeric) from the functional gene (Maglic et al, ). It, therefore, appeared that during alignment, reassignment of short reads containing pseudogene‐derived variants, from TMEM231 to the more closely‐matching pseudogene locus, was the explanation for the apparent loss of read‐depth at exon 4.…”
Section: Resultssupporting
confidence: 74%
“…We confirmed the presence of the conversion event by Sanger sequencing a 1187‐bp amplicon derived from the gene‐specific intron 3/exon 4 loci and showed that it was paternally inherited (Figure a). Two flanking pseudogene‐derived variants (c.742‐49G>A and c.823+4A>G) reported by Maglic et al () were not detected on the converted allele in our patient (data not shown); suggesting that the allele we have observed reflects a recurrent gene conversion event, rather than an ancestral founder allele.…”
Section: Resultssupporting
confidence: 44%
See 2 more Smart Citations
“…For example, presumed nonsense mutations in CC2D2A may cause Meckel syndrome (MKS) (MKS6 subtype), whereas missense mutations in the same gene lead to Joubert syndrome (JBTS) (JBTS9 subtype) 188 , suggesting that MKS and JBTS are caused by an allelic series that affects the same essential ciliary function. Similarly, different alleles of TMEM231 are associated with MKS, orofaciodigital syndrome (OFD) and JBTS, even within one family 101,111,189 .…”
Section: Figurementioning
confidence: 99%